2020
DOI: 10.1101/2020.08.11.20145086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Face Coverings and Respiratory Tract Droplet Dispersion

Abstract: Respiratory droplets are the primary transmission route for SARS-CoV-2. Evidence suggests that virus transmission can be reduced by face coverings, but robust evidence for how mask usage might affect safe distancing parameters is lacking. Accordingly, we investigate the effectiveness of surgical masks and single-layer cotton masks on mitigating dispersion of large respiratory droplets (i.e. non aerosol). We tested a manikin ejecting fluorescent droplets and human volunteers in speaking and coughing conditions.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…They found that the outward emission of micron-scale aerosol particles is reduced by 90% and 74% for speaking and coughing, respectively, when the source wears a mask. These results were complemented by Bandiera et al [6] who focused on the largest (10 µm -1000 µm) droplet. They tested both a speaking and coughing simulator as well as human volunteers, and found that even a single layer cotton mask blocks 99.9% of large droplets.…”
Section: Face Coverings Aerosol Dispersion and Mitigation Of Virus Tmentioning
confidence: 80%
“…They found that the outward emission of micron-scale aerosol particles is reduced by 90% and 74% for speaking and coughing, respectively, when the source wears a mask. These results were complemented by Bandiera et al [6] who focused on the largest (10 µm -1000 µm) droplet. They tested both a speaking and coughing simulator as well as human volunteers, and found that even a single layer cotton mask blocks 99.9% of large droplets.…”
Section: Face Coverings Aerosol Dispersion and Mitigation Of Virus Tmentioning
confidence: 80%
“…Our observation that uptake of COVID-19 prevention measures was low (ranging between 17 and 41%) amidst high awareness of how COVID-19 is spread and prevented raises serious public health concerns. Evidence shows that use of face-masks can reduce the spread of the coronavirus by up to 99.9% through reducing exhalation of large respiratory droplets [ 21 ], suggesting that universal use of face-masks, along with social distancing and hand-washing with soap and running water can substantially reduce the risk of coronavirus transmission at population level. Indeed, Bandiera et al [ 21 ] found that a person standing 2 m from someone coughing without a mask is exposed to over 10,000 times more respiratory droplets than from someone standing 0.5 m away wearing a basic single-layer mask.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that use of face-masks can reduce the spread of the coronavirus by up to 99.9% through reducing exhalation of large respiratory droplets [ 21 ], suggesting that universal use of face-masks, along with social distancing and hand-washing with soap and running water can substantially reduce the risk of coronavirus transmission at population level. Indeed, Bandiera et al [ 21 ] found that a person standing 2 m from someone coughing without a mask is exposed to over 10,000 times more respiratory droplets than from someone standing 0.5 m away wearing a basic single-layer mask. The low uptake of COVID-19 prevention measures reported among ABYM in Kampala, Uganda, could be related to low perceived risk of COVID-19 coupled with misinformation in some population sub-groups [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies make it clear that wearing various face coverings can significantly reduce the spatial extent of the frontal air flow ejected by a person while breathing or coughing. 138,139 Different mask designs and materials clearly affect the efficacy of reducing emission, 140 and the extent of such reduction during speech can be quantified by a new lowcost method. 141 We focus our discussion on fabric face masks.…”
Section: Face Masksmentioning
confidence: 99%